Czy na Śląsku doszło do ludobójstwa ekologicznego? - Nijakowski, Lech M. (Narracje o Zagładzie [czasopismo zamknięte], 2021)
The essay answers the question of whether ecocide occurred in the region of Upper Silesia. The paper includes a brief discussion on the concept of ecocide. The paper presents two cases of ecocide – one in West Papua and the other in Darfur. The prognosis of climate genocide in the future is also presented. The text argues that there was no intentional ecocide of Silesians in Upper Silesia, although ecological discrimination against them was observed.